Involvement of the Inconstant Bursa of the Fifth Metatarsophalangeal Joint in Psoriatic Arthritis: A Clinical and Ultrasonographic Study. (1st July 2014) - Ciancio, Giovanni; Volpinari, Stefania; Fotinidi, Maria; Furini, Federica; Farina, Ilaria; Bortoluzzi, Alessandra; Ferracin, Manuela; Bandinelli, Francesca; Orzincolo, Carlo; Trotta, Francesco; Govoni, Marcello
Abstract : Objective . To evaluate the involvement of the bursa located next to the head of the 5th metatarsal bone in patients with psoriatic arthritis (PsA) in comparison with the other seronegative spondyloarthritis (SpA). Methods . All patients with PsA seen during a period of 24 months were enrolled. The control group included healthy subjects and patients with the other SpA. All subjects underwent clinical and ultrasound (US) examination of the lateral surface of the 5th metatarsal. Results . 150 PsA patients (88 M; 62 F), 172 SpA (107 M; 65 F), and 95 healthy controls (58 M; 37 F) were evaluated. Based on clinical and US evaluation, bursitis was diagnosed in 17/150 (11.3%) PsA patients but in none of the SpA (P < 0.0001 ) and healthy (P = 0.0002 ) controls. In detecting bursitis, US was more sensitive than clinical examination, although the difference did not reach statistical significance (P = 0.09 ). Conclusion . The bursa of the 5th metatarsophalangeal joint appears to be involved in PsA more frequently than by chance. If confirmed by other studies, this finding could be considered as a distinctive clinical sign of PsA, useful for differential diagnosis with the other SpA. In asymptomatic patients, US proved to be more sensitive in the detection of bursitis.